Lean Healthcare for financial management in accredited hospitals: a bibliometric study of scientific production - Ribeiro, Tatiane Lemes Moreira; Melo, Isabela Crisóstomo; Tinoco, Cynara Mendonça Moreira (Brazilian Journal of Production Engineering, 2026)
The healthcare system faces chronic challenges related to overcrowding in hospitals, as well as long waiting times for care and growing pressure for greater efficiency in resource management. In this scenario, Lean Healthcare emerges with the goal of eliminating waste, standardising processes, and adding value to the patient. Despite the expansion of literature on the subject, there are still gaps in understanding research trends, the tools most used in accreditation processes, and the specific contexts for applying Lean methodology in hospital environments with a view to sustainability of results. This study aimed to conduct a systematic review of the literature to map scientific production based on the keywords “Lean Healthcare,” hospital, and standard*. The research is exploratory and descriptive in nature, with a qualitative and quantitative approach. The Web of Science and Scopus databases were used, first without filters and then with a time frame from 2010 to 2025. Data analysis was conducted in RStudio, with Bibliometrix, revealing progressive growth in publications over the last ten years and identifying a lack of studies relating Lean to financial indicators, pointing to an opportunity for research that integrates the Lean Healthcare methodology with hospital economic and financial management.